Vedic River Sarasvati and Hindu civilization - Conference on "Vedic River Sarasvati and Hindu Civilization" 2008 : India International Centre; Kalyanaraman, S. 1939-; Sarasvati Research and Education Trust (Chennai, India) (New Delhi : Aryan Books International in association with Sarasvati Research and Educational Trust, 2008)
Contributed papers presented at a conference held at IIC, New Delhi from Oct. 24 to 26, 2008.
Keywords: Hindu civilization -- Congresses; Vedic literature -- History and criticism -- Congresses; Saraswati River (India) -- Civilization